Proposed Steps to Address Excessive Delays in the Completion of Article IV Consultations. (Policy Papers; Policy Paper ;, 2012)
Bilateral surveillance is mandatory for both the Fund and its members, and all members have an obligation to consult with the Fund for this purpose.3 Periodic consultations with members on their policies and access to necessary information are essential for effective bilateral surveillance. Furthermore, to enable the Fund to effectively conduct multilateral surveillance, bilateral surveillance needs to cover all economies at a reasonable frequency.